Subgroup analysis of East Asian patients in REGARD: A phase III trial of ramucirumab and best supportive care for advanced gastric cancer. Issue 3 (10th January 2018) - Chung, Hyun Cheol; Kok, Victor C.; Cheng, Rebecca; Hsu, Yanzhi; Orlando, Mauro; Fuchs, Charles; Cho, Jae Yong
Abstract: Aim: We describe a subgroup analysis assessing the efficacy and safety of ramucirumab monotherapy in East Asian (EA) patients from the REGARD trial. Methods: Patients with advanced gastric or gastroesophageal junction adenocarcinoma with progressive disease were randomized 2:1 to receive ramucirumab (8 mg/kg) plus best supportive care (BSC) or placebo plus BSC every 2 weeks. Post hoc subset analyses were performed on the EA and non‐EA intention‐to‐treat populations. Results: Of 355 intention‐to‐treat patients, 26 patients from EA were randomized to ramucirumab ( n = 18) or placebo ( n = 8). Median overall survival was 6.5 months in the ramucirumab arm and 4.8 months in the placebo arm (hazard ratio [HR] 0.69; 95% confidence interval [CI], 0.27–1.82) for EA patients, and 5.2 months in the ramucirumab arm and 3.8 months in the placebo arm (HR 0.78; 95% CI, 0.60–1.02) for non‐EA patients. The rate of disease control was numerically higher in ramucirumab patients versus placebo; 61% versus 38% respectively for EA patients, and 48% versus 22% for non‐EA patients. The incidence of grade ≥3 treatment emergent adverse events was higher in the ramucirumab arm compared to placebo (39% vs 13%). Conclusion: Despite limitations, this subgroup analysis suggests that ramucirumab monotherapy improves efficacy outcomes with a tolerable safety profile in EA patients with previously treated advanced gastric cancer.